Cytotoxicity and Oral Acute Toxicity Studies of Lantana camara Leaf Extract - Badakhshan Mahdi Pour; Sreenivasan Sasidharan; Lachimanan Yoga Latha (Molecules, 2011)
Background: The objective of this study was to investigate the toxicity of Lantana camara methanol extract. Methods: In order to evaluate the toxicity of Lantana camara, the acute toxicity of the methanolic extract on adult mice and cytotoxicity test on Vero cell line were investigated. A fixed large dose of 2 g/kg body weight of L. camara leaf extract was administrated by a single oral gavage according to the OECD procedure. Results: In 2 weeks, L. camara leaf extract showed no obvious acute toxicity. While female mice lost body weight after being treated with single dose of leaf extract in acute toxicity test, male ones lost organ mass, particularly for heart and kidney. The biochemical liver function tests showed significantly elevated TBIL and ALT in the L. camara leaf extract treated female mice group compared with the control group. Cytotoxicity effect of leaf extract of L. camara was estimated through a MTT assay. Cytotoxicity tests on Vero cell line disclosed that leaf extract at concentrations up to 500 µg/mL inhibited the growth of cells 2.5 times less than did Triton 100× 1%. More interestingly, the cytotoxicity initiated to decline at elevated concentrations of this extract. Conclusions: The results of both tests confirm that L. camara shows a pro toxic effect.